Influence of simulated pulpal pressure on efficacy of bleaching gels - Borges, Alessandra Bühler [UNESP]; Batista, Graziela Ribeiro [UNESP]; Arantes, Paula Tamião [UNESP]; Wiegand, Annette; Attin, Thomas; Torres, Carlos Rocha Gomes [UNESP] (Jaypee Brothers Medical Publishing, 2014)
The aim of this study was to investigate the Influence of simulated pulpal pressure on efficacy of bleaching gels. Cylindrical enamel-dentin specimens from bovine teeth (3 mm diameter, enamel and dentin layer each 1 mm thick) were divided into 4 groups, according to the bleaching treatment: negative control (non-bleached), bleached with 10% carbamide peroxide (CP), bleached with 7.5% hydrogen peroxide (HP) and bleached with 35% hydrogen peroxide. Ten percent CP gel was applied for 8 h/day and 7.5% HP for 1 h/day, during 14 days. For 35% HP treatment, two sessions of 45 minutes each were employed. In intermediate periods specimens were stored in artificial saliva. Experimental groups (n = 19) were subdivided according to the simulation of pulpal pressure (25 mm Hg) during bleaching treatment. Initial color measurement and after bleaching treatment were assessed by spectrophotometry, using CIE L*a*b* system. The data were statistically analyzed by ANOVA and Dunnett's post-hoc tests (p < 0.05). There was significant difference of ΔE for all experimental groups compared to negative control group, according to Dunnett's test (p < 0.0001). There were no significant difference for total color variation (ΔE) among experimental groups (p > 0.05). It was concluded that all bleaching gels showed bleaching efficacy compared to non-bleached group and that the simulated pulpal pressure did not Influence the bleaching outcomes of the tested gels. Although numerous in vitro studies investigating the efficacy of bleaching agents have been performed, they do not properly simulate the pulpal pressure. In order to make these studies closer to clinical conditions, it is important to reproduce these conditions in laboratory, so the results can be more reliable. This in vitro study was performed under simulated pulpal pressure, aiming to investigate its Influence on dental bleaching outcomes.
Keywords: Dental bleaching; Simulated pulpal pressure; Bovine teeth